First evidence for the joint dispersal of mycorrhizal fungi and plant diaspores by birds - Correia, Marta (2019)
Seed dispersal allows plants to colonise new sites and escape from pathogens and intraspecific competition, maintaining plant genetic diversity and regulating plant distribution. Conversely, most plant species form mutualistic associations with arbuscular mycorrhizal (AM) fungi in a symbiosis established immediately after seed germination. Because AM fungi are obligate symbionts, using the same dispersal vector as their host should be highly advantageous for their survival, but the co-dispersal of seeds and AM fungal spores has never been confirmed. We aim to clarify the potential role of European birds, essential dispersers for many plant species, as co-dispersers of seeds and AM fungal spores. In total, 63 bird droppings with intact seeds were placed in sterilised soil and maintained for 4 months in a protected environment to avoid contamination. Additionally, 173 bird droppings and 729 gauze swabs used to clean birds' feet were inspected for AM fungal spores. Although no spores were detected by direct observation of these samples, seven Rubus ulmifolius seedlings obtained from four independent droppings of Erithacus rubecula and Sylvia melanocephala were colonised by AM fungi. Our results show that birds can effectively co-disperse viable seeds and AM fungal spores, potentially over long distances, providing a pivotal mechanism to understand the cosmopolitan distribution of AM fungi.